Five years ofit management improvement Eight cases from the Master of IT Management - Alumni, Eight (IOS Press, 2013)
It has now been five years since the launch of the postgraduate Master of IT Management at TU Delft. A host of students have now completed the programme. This publication showcases the results of a handful of these graduates. It presents summaries of eight theses written between 2003 and 2008, selected to provide an excellent picture of the full range of graduation projects.